Incidence of cutaneous Leishmaniasis in humans during the COVID-19 pandemic in Baluchistan Province, Pakistan - Syeda Atiya Bukhari; Lamia Shafqat; Khawar Bilal; Ashiq Hussain; Shaista Gul; Shumaila Naz; Naseer Ali Shah; Emina Dervišević; Lejla Dervišević; Zurifa Ajanović; Hajra Manahil; Muhammad Aamir Ghafoor Chaudhary; et al. (Journal of Infection in Developing Countries)
Introduction: Cutaneous leishmaniasis (CL) is one of the neglected tropical diseases that affects impoverished communities throughout the world. In Pakistan CL is an endemic disease.